Adaptation and visual discomfort from flicker. (July 2019) - Yoshimoto, Sanae; Jiang, Fang; Takeuchi, Tatsuto; Wilkins, Arnold J.; Webster, Michael A.
Abstract: Spatial images with unnatural amplitude spectra tend to appear uncomfortable. Analogous effects are found in the temporal domain, yet discomfort in flickering patterns is also strongly dependent on the phase spectrum. Here we examined how discomfort in temporal flicker is affected by adaptation to different amplitude and phase spectra. Adapting and test flicker were square wave or random phase transitions in a uniform field filtered by increasing (blurred) or decreasing (sharpened) the slope of the amplitude spectrum. Participants rated the level of discomfort or sharpness/blur for the test flicker. Before adaptation, square wave transitions were rated as most comfortable when they had "focused" edges, which were defined as characterized by 1/ f amplitude spectra, while random phase transitions instead appeared more comfortable the more blurred they were. After adapting to blurred or sharpened transitions, both square wave and random phase flicker appeared more sharpened or blurred, respectively, and these effects were consistent with renormalization of perceived temporal focus. In comparison, adaptation affected discomfort in the two waveforms in qualitatively different ways, and exposure to the adapting stimulus tended to increase rather than decreased its perceived discomfort. These results point to a dissociation between the perceived amplitude spectrum and perceived discomfort, suggesting they in part depend on distinct processes. The results further illustrate the importance of the phase spectrum in determining visual discomfort from flickering patterns.